An Introduction to Organ and Tissue Donation (Out of Print) - Judith Tamburlin; Joan Kruegler (Association of American Medical Colleges, 2010)
Abstract This resource is a webcast designed to provide students with information about organ donation as well as to prepare them to educate their patients on this topic. Students will be informed about organs and tissue that can be transplanted, the types of donation, the definition of brain death, the determination of brain death, criteria for identifying potential organ donors, and organ matching criteria. Students will also identify the role of organ procurement organizations (OPO) and the United Network for Organ Sharing (UNOS) as well as understand their role in educating their patients. The importance of making an informed decision about one's wish to donate organs and documenting this through state donor registry enrollment and advanced directives will be discussed. Upon completion of this program, students will have increased self-efficacy in communicating with patients about organ donation. Students will also be better informed to make their own decisions regarding organ donation. This webcast can be accessed via the internet. On its own it will provide a cost-effective, time-efficient mechanism for providing education on the topic of organ donation. This webcast can be shown to students prior to a lecture on organ donation, given by a transplant surgeon or OPO professional. In addition, supplemental activities with standardized patients will enhance the quality of the experience through communication feedback and reinforcement of the lecture and audio-visual material.